2011
DOI: 10.1080/17458080.2010.517571
|View full text |Cite
|
Sign up to set email alerts
|

Nano-metal oxide: potential catalyst on thermal decomposition of ammonium perchlorate

Abstract: In this review, an attempt to collect the summarised data of literature on catalytic effect of nano-oxides, such as mono oxides, mixed oxide, binary and ternary ferrites and rare earth metal oxides on the thermal decomposition of ammonium perchlorate (AP) is made. Influence of size effect of oxides on thermal decomposition of AP and comparison of bulk and nanosized oxides is also discussed here. Several experimental results revealed that due to small size and large surface area nanosized metal oxides are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(41 citation statements)
references
References 80 publications
(90 reference statements)
0
41
0
Order By: Relevance
“…At present, it is well known that a scheme of thermal decomposition of ammonium perchlorate as a version of proton mechanism proposed by Jackobs can be presented as follow [18]: The most essential feature of the thermal decomposition of AP is the two stages decomposition, low-temperature decomposition, and high-temperature decomposition commonly referred as LTD and HTD, respectively [15]. At first, a proton passing from the ammonium ion to perchlorate ion becomes mobile and then the gaseous NH 3 [20]. However, the decomposition behavior of AP will be different with the help Cu-Cr-Pb nanocomposites as compared to the pure AP.…”
Section: Catalytic Properties Of Cu-cr-pb Nanocompositesmentioning
confidence: 99%
“…At present, it is well known that a scheme of thermal decomposition of ammonium perchlorate as a version of proton mechanism proposed by Jackobs can be presented as follow [18]: The most essential feature of the thermal decomposition of AP is the two stages decomposition, low-temperature decomposition, and high-temperature decomposition commonly referred as LTD and HTD, respectively [15]. At first, a proton passing from the ammonium ion to perchlorate ion becomes mobile and then the gaseous NH 3 [20]. However, the decomposition behavior of AP will be different with the help Cu-Cr-Pb nanocomposites as compared to the pure AP.…”
Section: Catalytic Properties Of Cu-cr-pb Nanocompositesmentioning
confidence: 99%
“…In a comparative study with various types of iron oxides ranging from 30 m to 4-10 nm, Reina et al showed that NANOCAT Ultrafine Iron Oxide could increase up to 100 % the burn rate of non-catalyzed propellant [13]. An extensive research regarding effect of burn rate catalysts has been carried out in the past [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that copper(II) oxide nanocrystals are a suitable additive for catalytic decomposition of AP, and can significantly reduce the HTD temperature and increase the heat released with respect to pure AP [23]. This action of CuO can be considerably improved by decreasing its particle size to the nanometer scale [24].…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that the nitrate salt was a better precursor, and thus was employed in further experiments. There have been many studies on the mechanism of the effect of nanoparticles as catalysts in the thermal decomposition of AP, but this still remains unresolved [24]. However, from these studies two mechanisms were proposed which are based on the proton and electron transfer theory and are associated with the LTD and HTD, respectively [38].…”
Section: Catalytic Activitymentioning
confidence: 99%